Optimization of urban thermal environment for indonesia coastal-climate urban area: a microclimatic modeling - Gunawan, Kelvin Narada; Zidane, Chairil; Koerniawan, M Donny (Universitas Gadjah Mada, 2024)
Coastal urban areas, one of which is the PIK 2, Tangerang Regency, Indonesia, as the study case, have distinctive climate characteristics: changes in land and sea breezes during different seasons and high humidity and wind speed levels, which affect thermal comfort. The optimal building mass needs to be studied to achieve ideal thermal comfort conditions, which can effectively respond to climate characteristics different from those of other urban areas. This paper investigates the existing urban thermal environment and models the impact of building orientation, form, and H/W ratio simulated in ENVI-met. Based on the study findings, it has been determined that positioning a building diagonally towards the sea at a 45-degree angle effectively reduces excessive wind speeds, resulting in a favorable PMV score. Additionally, incorporating a sky bridge into the building form design provides adequate shading and contributes to achieving optimal thermal comfort in coastal-climate urban areas. Moreover, the optimal H/W ratio is 0.5, which can reduce wind speed without significantly lowering the temperature, thereby maintaining thermal comfort.